Genetic variation of selected Camellia sinensis (Cultivated Tea) varieties in Malaysia based on random amplified microsatellite (RAMs) markers - Latip, S. N. H.; Muhamad Awang, Rita; Manjeri, G.; Tan, Soon Guan (Universiti Putra Malaysia Press, 2010)
Studies on the genetic variation among Camellia sinensis L. varieties (cultivated tea) in Malaysia were conducted by using RAMs markers. Six varieties were selected from Sungai Palas Boh Estate, Cameron Highlands and nine varieties were selected from Bukit Cheeding Boh Estate, Banting. These tea varieties were classified as resistant, intermediate, or susceptible varieties based on the level of infestation by the mosquito bug, Helopeltis theivora. DNA was extracted from the leaves of 225 individuals belonging to different varieties from the two populations. Four RAMs primers were used to evaluate the genetic variation in 15 varieties of tea. Distances were calculated based on Nei and Li’s (1979) similarity coefficients using the data from the RAMs markers. A cluster analysis employing UPGMA was done and the dendrogram grouped the tea varieties into two clusters with intermediate variety grouping and the resistant (the first cluster) or susceptible (the second cluster) varieties. The first cluster consisted of all the varieties from Cameron Highlands, except for BC223 (resistant) and 63/14 (resistant) from the Banting population, while the other clusters consisted of all the varieties from the Banting population, except for BC196 (resistant) from the Cameron Highlands population. The dendrogram showed that the genetic differences were based on the populations’ geographical distributions and partially based on their resistance towards attack by H. theivora.